PENGARUH KEPUASAN KERJA TERHADAP KESEHATAN MENTAL KARYAWAN DI PT X - Arfian Arfian; Fadila Fatih Arasyid, Jesika Adriana Panjaitan (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This research was conducted to investigate how job satisfaction impacts the mental health of workers at PT. X Tbk. The type of research used in this journal is a qualitative study. The data collection carried out in this research took the form of interviews with 5 employees at PT X Tbk. This research is aimed at understanding how important job satisfaction is to the mental health of employees who work in physical training centers or PT at PT. X Tbk. In this research, qualitative data collection methods were used. Primary data was collected through interviews and internet searching. This research is aimed at determining the relationship between job satisfaction and mental health among employees at PT X Tbk. This research was conducted as part of a survey of PT X Tbk employees using the interview method to measure their level of job satisfaction and mental health. Research findings show a positive relationship between employee job satisfaction at PT. X Tbk and their mental health. Regression analysis and descriptive statistics were used to analyze the collected data. Employees who are satisfied with their jobs tend to have lower stress levels, are more motivated, and have better overall mental health. This research shows that HR (Human Resources) management efforts are very important in achieving increased employee job satisfaction as a way to improve mental health in the workplace. This study makes an important contribution to understanding the factors that influence employee mental health in specific work environments.